Flash Card Implementation in Arabic Vocabulary Learning: Penerapan Kartu Flash dalam Pembelajaran Kosakata Bahasa Arab - Imron Suwantoro; Najih Anwar (Indonesian Journal of Innovation Studies, 2025)
General Background: Arabic vocabulary mastery is an essential component in developing students’ language skills and communication abilities in Arabic learning. Specific Background: Students in class X at SMA Muhammadiyah 2 Sidoarjo come from diverse educational backgrounds, causing differences in familiarity with Arabic vocabulary learning. Flash card media containing images and Arabic text were applied to support mufradat learning activities. Knowledge Gap: Previous studies discussed flash card media in Arabic learning using different methods and settings, while limited studies examined the implementation process together with supporting and inhibiting factors in senior high school Arabic vocabulary learning. Aims: This study aimed to identify the implementation of flash card media in Arabic vocabulary learning and to describe the supporting and inhibiting factors in class X at SMA Muhammadiyah 2 Sidoarjo. Results: The study found that flash card implementation was conducted through planning, learning activities, reinforcement, and evaluation stages using image-based cards, repetition techniques, and interactive games. Supporting factors included visual memorization support, active student participation, practicality, flexibility, and interactive learning activities. Inhibiting factors included limited material coverage, distraction during learning, technical constraints in digital use, visual limitations, and dependence on teacher skills. Novelty: This study provides a qualitative implementation analysis of flash card media in Arabic mufradat learning within the context of students with varied educational backgrounds at SMA Muhammadiyah 2 Sidoarjo. Implications: The findings contribute to Arabic language learning practices by providing insights into the use of flash card media for classroom-based mufradat instruction and identifying factors that should be considered during implementation.Highlights: Visual cards and repetition activities supported students in recalling Arabic vocabulary during classroom sessions. Interactive games encouraged active participation and increased student confidence in responding to learning tasks. Technical limitations, restricted material scope, and classroom conditions became barriers during media application. Keywords: Flash Card Media; Arabic Vocabulary Learning; Mufradat Instruction; Qualitative Analysis; Classroom Implementation